2019
DOI: 10.22456/2238-152x.86774
|View full text |Cite
|
Sign up to set email alerts
|

Gestão Autônoma da Medicação: saberes e visibilidades de usuários de saúde mental em universidades no interior do RS

Abstract: Este artigo abordou os efeitos de uma pesquisa da estratégia da Gestão Autônoma da Medicação em usuárias(os) da saúde mental que passam a ocupar o lugar de palestrantes em ambientes acadêmicos no interior do RS. Por objetivo geral pretendeu analisar como se constituíram esses investimentos e visibilidades no saber das(os) usuárias(os) para frequentarem essas universidades. Também intentou-se descrever as relações de saber e poder e os limites da prática de autonomia nas salas de aula. Por uma abordagem de insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…To analyze the experiences of mental health service users with the development of the Medication Management Guide (GAM) group Nine studies reported on a multicentric study in partnership with a Canadian university that translated and implemented a medication management guide in community mental health centers in several regions of Brazil (Jorge et al, 2012;Onocko Campos et al, 2012;Emerich et al, 2014;Silveira et al, 2014;Gonçalves and Campos, 2017;Chassot and da Silva, 2018;Senna and Azambuja, 2019;Palombini et al, 2020;Passos et al, 2020). Seven studies reported using principles of Guba and Licoln's fourth-generation evaluation, a constructivist methodfocused on negotiationthat engages stakeholder groups across all phases in iterative processes to reach consensus Lincoln, 1989, 2001;Kantorski et al, 2009;Onocko Campos et al, 2009;Jorge et al, 2012;Emerich et al, 2014;Moreira and Onocko-Campos, 2017;Alves et al, 2018;Palombini et al, 2020).…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the experiences of mental health service users with the development of the Medication Management Guide (GAM) group Nine studies reported on a multicentric study in partnership with a Canadian university that translated and implemented a medication management guide in community mental health centers in several regions of Brazil (Jorge et al, 2012;Onocko Campos et al, 2012;Emerich et al, 2014;Silveira et al, 2014;Gonçalves and Campos, 2017;Chassot and da Silva, 2018;Senna and Azambuja, 2019;Palombini et al, 2020;Passos et al, 2020). Seven studies reported using principles of Guba and Licoln's fourth-generation evaluation, a constructivist methodfocused on negotiationthat engages stakeholder groups across all phases in iterative processes to reach consensus Lincoln, 1989, 2001;Kantorski et al, 2009;Onocko Campos et al, 2009;Jorge et al, 2012;Emerich et al, 2014;Moreira and Onocko-Campos, 2017;Alves et al, 2018;Palombini et al, 2020).…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…No Senna and Azambuja (2019) Balancing power differentials between researchers and participants. Research with and not about participants.…”
Section: Nomentioning
confidence: 99%
“…La GAM se ha guiado por la cogestión 18 y la autonomía 19,21,22 como ejes centrales de su práctica y dichas acciones conciernen no sólo a la conceptualización del término, sino también y principalmente a "las performances de la autonomía" 21 ; es decir, trata de responder a la pregunta de en qué condiciones y criterios son posibles las acciones de autonomía en el contexto de la salud mental. De este modo, antepone a la pregunta de si "los usuarios de salud mental son autónomos" otra cuestión: "¿cuándo es posible la autonomía en la salud mental?".…”
Section: Performar La Autonomíaunclassified
“…Así, la autonomía puede entenderse como: a) ampliación de la capacidad de decisión de los usuarios de salud mental en su proceso de atención. Esta se produciría, a través de la desestabilización de las relaciones de poder entre el médico y el "paciente" [22][23][24][25] y la puesta en común de experiencias con el grupo en un proceso de ayuda mutua y de acceso a conocimientos y derechos 23 .…”
Section: Performar La Autonomíaunclassified
“…En este sentido, proyectos de investigación colaborativa e intervención participativa han otorgado una mayor comprensión a los determinantes contextuales de la salud mental. En este marco, se han publicado diversos estudios en torno a la Gestión Autónoma de la Medicación (GAM) en Brasil que abordan las narrativas de usuarios de salud mental sobre el tratamiento farmacológico (COUGO, 2018; FERRER; PALOMBINI; AZAMBUJA, 2020; FERREIRA; FEITOSA; AMORIM, 2020; PAZOS; SADE; MACERATA, 2019;ROSA, et al, 2020;SENNA;ZANCHET;.…”
Section: Nuevas Concepciones De Los Derechos De Ciudadanía Y Reconfig...unclassified